Skärgårdskapell i Norden: En kortfattad översikt med några reflexioner - Westerdahl, Christer (Hikuin, 2006)
Archipelago chapels of the North. A brief survey with some reflections By Christer Westerdahl During the High and Late Middle Ages it seems that quite a number of maritime chapels were built and used in the archipelagoes of the North. The period is roughly the middle of the 14th to the middle of the 16th century, with varying factors of Lent enforcement and of the ensuing state of the international fish markets. These datings have, however, seldom been proved at the individual sites. Neither has a comparative perspective been used very often within this immense area. Most chapels are directly attached to harbours, presumably either for fishing or for shipping, some for both. The main emphasis is with some cases at the coasts of Agder, South Norway, but the scope is all- Nordic. Some of these harbours continue to be used during a long time. Their chapels may be used, reused, moved or rebuilt into Lutheran times. During the 17th and 18th centuries were built an even larger number of fishing chapels, especially on the Swedish northern side the Baltic, in the middle parts of the Bothnian Sea. These chapels have a background in long-range fishing by burghers of Gävle and other towns in the Baltic, north of Stockholm and towns situated at lake Mälaren west of Stockholm. The archipelagoes of Finland have a number of chapels which seem to have a combined background in seafaring and fishing. Some sites have been supposed to be intentionally connected to islands mentioned in the earliest Baltic sea itinerary sequence c. AD 1300. Within the borders of medieval Denmark there are few of this island type of chapel, mainly since the definition of a Scandinavian archipelago does not apply here. The whole area has got a number of separate burial sites for drowned sailors. Some of these probably had a chapel as well. The author tries to sketch types of indications of unknown chapel sites, such as place names, oral tradition as well as the position of these sites in a context of a non-Christian ritual landscape, with foundation myths associated with virgins and other female beings, of local and regional power and of service for fishermen and sailors, questions on the causes for the erection of chapels, problems in identification of remains and the probable dating in an all-Nordic perspective.